Germinação e disseminação endozoocórica de sementes de forrageiras nativas do bioma Pampa - (:unkn) unknown (Universidade Federal do Pampa, 2017)
The Pampa Biome in southern Brazil has ample floristic diversity in the most diverse field formations. The native field provides forage to the gaucho livestock and at the same time has its characteristics preserved, when used properly. Agriculture currently occupies areas previously intended for pasture, thereby, there were changes in occupation and fodder management. Once loss of diversity in degraded areas occur, initiative efforts in the search for maintenance and conservation of the Pampas Biome should be investigated. The seeds of the native species have the role of regeneration of the field, and knowledge of the germination process is fundamental to any form of pasture recovery. The dissemination of seeds is another point, the zoocoric dispersion can be a tool during the process. In this way, the objective of this work was to characterize germination, vigor, dormancy, and endozoochoric dispersion with native species of the Pampa Biome. The work was conducted at DPPA (São Gabriel/RS) and at UNIPAMPA (Itaqui/RS). The seeds were collected from natural fields. Three experiments were carried out, in the first moment was characterized vigor and germination of 23 species. After, a second experiment was conducted with six species, this one sought to point out possible methods for overcoming dormancy. The last experiment evaluated the endozoochory process in cattle, testing two species of wide distribution. It was characterized the recovery of the seeds in the feces and the effect on vigor, germination and viability. The data statistically evaluated by the Tukey test at 5% of error probability. The values of vigor and germination are quite different, but for most species low values were found. Some species respond to dormancy overcoming treatment. There was recovery of the seeds in the feces, with reduction in the volume excreted. Vigor and germination do not decrease after passage through the gastrointestinal tract, but the viability of Desmodium incanum reduced. There are differences among species for vigor, germination and dispersal.
Keywords: Dispersal; Dormancy; Forage; Germination; Pampa biome; Seed; Bioma Pampa; Disseminação; Dormência; Forrageira; Germinação; Semente; CNPQ::CIENCIAS AGRARIAS